PELATIHAN PEMBELAJARAN INOVATIF MELALUI PEMBUATAN VOICE THREADS, BLOGGING, SOCIAL BOOKMARKING, SINIAR ATAU PODCAST DAN SCREENCAST DI SMAN 10 KOTA BENGKULU (Universitas Bengkulu, 2024)
SMAN 10 Bengkulu City is one of the Senior High Schools in Bengkulu City which has implemented independent Curriculum. This curriculum allows teachers to apply learning methods and develop teaching materials independently. This requires teachers to have skills in designing innovative learning. We conducted a community service program aiming to train teachers on innovative learning through creating Voice Threads, Blogging, Social Bookmarking, Podcasts, and Screencasts. This program was initiated by introducing Voice Threads, Blogging, Social Bookmarking, Podcasts, and Screencasts. We also demonstrate how to use them in creating innovative learning. Afterwards, we allowed the participants to give question in question answer section. At the end of the program, we sent a quistionaire to obtain a feedback of the program. The data showed that this program is useful for them as a teacher because it is something new and can improve their knowledge. This was also insightful to design innovative learning. Overall, they were satisfying with this program.